Caracterización morfológica e identificación de zonas potenciales de conservación de copal (dacryodes peruviana) en los siete transectos del proyecto banco de germoplasma - Alvarez Tacunga, Daniel Mauricio (2017)
To the Copal (Dacryodes peruviana) morphologically characterizing was the objective in this following research in order to identify areas that have a potential species conservation. The Germplasm Bank transects project are distributed in Pujilí city, La Esperanza parish, La Mana city, the Copal tree species were found in the transects 2, 3 and 4 belonging to La Esperanza parish which 3 samples were collected for each transect, 24 descriptors were taken that helped to characterize morphologically those species, among them 18 qualitative variables and 6 quantitative variables, in order to obtain the data, a statistical analysis percentage, which helped to identify small changes in the qualitative characteristics of the oak and was made a data table to analyze the quantitative characteristics, in addition a dendogram was made which allowed to observe the morphological variability between samples collected. The statistical analysis determined there is very little variation in the copal qualitative and quantitative characteristics, however the conglomerates statistical analysis was able to identify 2 groups, in which the largest conglomerate shows that the samples of the transect 3 and 4 have a greater similarity in their morphological characteristics therefore, it was concluded that these transects have the greatest potential for the conservation of the copal (Dacryodes peruviana)